Benz-amidinato calcium iodide catalyzed aldehyde and ketone hydroboration with unprecedented functional group tolerance - Yadav, S.; Pahar, S.; Sen, S. S. (Chemical Communications, 2017)
A benz-amidinato calcium compound, [PhC(NiPr)(2)Cal] (1), catalyzed hydroboration of a wide range of aldehydes and ketones using pinacolborane (HBpin) at room temperature is reported. The catalyst shows functional group tolerance even towards OH and NH groups. The strategy was further extended to imines.

C‐F bond activation by saturated NHC: mesoionic compound formation and its unprecedented adduct with B(C6F5)3 - Pait, M.; Kundu, G.; Tothadi, S.; Karak, S.; Jain, S.; Vanka, K.; Sen, S. S. (Angewandte Chemie - International Edition, 2019)
The reaction of SIPr, [1,3‐bis(2,6‐diisopropylphenyl)‐imidazolin‐2‐ylidene] (1), with C6F6 led to the formation of an unprecedented mesoionic compound (2). The formation of 2 is made accessible by deprotonation of the SIPr backbone with simultaneous elimination of HF. The C−F bond para to the imidazolium ring in 2 is only of 1.258(4) Å, which is the one of the shortest structurally authenticated C−F bonds known to date. The liberation of HF during the reaction is unequivocally proved by the addition of one more equivalent of SIPr, which leads to the imidazolium salt with the HF2− anion. To functionalize 2, the latter reacted with B(C6F5)3 to give an unusual donor–acceptor compound, where the fluoride atom from the C6F5 moiety coordinates to B(C6F5)3 and the carbanion moiety remains unaffected. Such coordination susceptibility of the fluoride atom of a nonmetallic system to a main‐group Lewis acid (Fnon‐metal→BR3) is quite unprecedented.
Keywords: C-F activation; carbanions; N-heterocyclic carbenes; structure elucidation; Ylides

Reactivity, bonding and structural elucidation of pendant methyl-pyridinato beta-diketiminate ligand moiety - Pahar, S.; Sen, S. S. (Acta Crystallographica A-Foundation and Advances, 2021)
Keywords: Flexibility of beta-diketiminate ligand; six-membered dialane heterocycle: an analogue of cyclohexane; structural diversity; Transmetallation among two p-block elements